2013
DOI: 10.1038/jid.2013.255
|View full text |Cite
|
Sign up to set email alerts
|

Selective Ablation of Glucocorticoid Receptor in Mouse Keratinocytes Increases Susceptibility to Skin Tumorigenesis

Abstract: We recently demonstrated that mice lacking the epidermal glucocorticoid (GC) receptor (GR) (GR epidermal knockout (GR(EKO)) mice) have developmental defects and sensitivity to epidermal challenge in adulthood. We examined the susceptibility of GR(EKO) mice to skin chemical carcinogenesis. GR(EKO) mice treated with a low dose of 12-dimethylbenz(a) anthracene (DMBA) followed by phorbol 12-myristate 13-acetate (PMA) promotion exhibited earlier papilloma formation with higher incidence and multiplicity relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
3
20
0
2
Order By: Relevance
“…We used a GR deficient cell line derived from adult GR EKO epidermis to unequivocally determine the dependence of Dex-induced changes in gene expression on this TF ( Fig. 3C; Latorre et al, 2013). In GR EKO cells, neither Tsc22d3 nor Zfp36 was induced by Dex, showing that the presence of GR is necessary for this process (Fig.…”
Section: Dex Induces Binding Of Gr and Klf4 In A Gr-dependent Mannermentioning
confidence: 98%
“…We used a GR deficient cell line derived from adult GR EKO epidermis to unequivocally determine the dependence of Dex-induced changes in gene expression on this TF ( Fig. 3C; Latorre et al, 2013). In GR EKO cells, neither Tsc22d3 nor Zfp36 was induced by Dex, showing that the presence of GR is necessary for this process (Fig.…”
Section: Dex Induces Binding Of Gr and Klf4 In A Gr-dependent Mannermentioning
confidence: 98%
“…This phenotype is recapitulated in keratinocyte specifi c GR KO mice generated using cre lox technology and keratin14-cre mice [ 30 ]. These epidermal GR KO mice also have increased susceptibility to chemical induced skin tumors [ 31 ]. Overexpression of GR in transgenic mice driven by the keratin5 promoter results in abnormal skin including hypoplasia and impaired hyperplastic response to topical TPA [ 32 ].…”
Section: Skinmentioning
confidence: 97%
“…In fact, the analyses of mouse models with epidermal-specific GR overexpression or inactivation demonstrated that GR exerts tumor suppressor actions during skin carcinogenesis [80,84]. GR EKO mice subjected to the classical two-stage protocol-consisting in a single low-dose application of the mutagen 12-dimethylbenz(a) anthracene (DMBA) followed by repeated PMA treatments-exhibited earlier papilloma formation with higher incidence and multiplicity, as well as increased tumor size relative to controls [83]. Also, papillomas in GR EKO mice displayed signs of early malignization, including delocalized expression of laminin A, dermal K5-positive cells, abnormal expression of K13, and focal loss of E-cadherin.…”
Section: Keratinmentioning
confidence: 99%